Human Activity Recognition on Smartphone: A Classification Analysis - Shianghau Wu; Yanan Song (Institute of Advanced Engineering and Science, 2014)
The study hinged on the human activity recognition on smartphones by using the random forests model and Ada Boost model to make the classification. The study compared the classification results of two models and found the AdaBoost model had the better classification results. The study also found the Ada Boost model had the advantage of less calculation time.